Pengaruh Model Pembelajaran SAVI (Somatis, Auditori, Visual, dan Intelektual) terhadap Kemampuan Komuniasi Matematika Siswa - Elya Rosalina; Harumi Citra Pertiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of the SAVI learning model (Somatic, Auditory, Visual, and Intellectual) on the mathematical communication skills of eighth grade students of Karang Dapo State Junior High School 2016/2017 academic year. This study uses the True Experimental Design method (pure experiment) with the research design used is the pretest posttest control group. Data analysis techniques used were normality test, homogeneity test and t-test. The study was conducted in class VIII of Karang Dapo Public Middle School in the 2016/2017 school year. 5 (five) meetings were held, with details of 3 (three) learning meetings, 1 (one) pretest and 1 (one) posttest. Of the 103 students who were members of 4 classes VIII, a random sample was taken with the aim that all classes have the same opportunity to become samples. Based on the results of data analysis with a significant level α = 0.05. The average score of mathematics communication skills of the experimental class students was 25.64 and the control class was 17.02. In conclusion, there is a significant influence of the SAVI learning model (Somatic, Auditory, Visual, and Intellectual) on the mathematical communication skills of Grade VIII students of Karang Dapo Public Middle School. Keywords: SAVI, Communication, Mathematics